Applying Wasatiyyah approach in de-radicalization programs - Yousif, Ahmad; El-Muhammady, Ahmad (Routledge, 2020)
De-radicalization program, essentially aims at changing the violent mind and behaviour through dialogue, heart-to-heart conversations, and re-learning in educational environment. Today, the concept of de-radicalization receives growing attention from researchers and policy-makers, partially due to failure of tackling extremism via hard approaches, i.e. detention. Worst, in some cases, prison becomes a fertile ground for radicalization. Like it or not, de-radicalization, or in some countries, it is called rehabilitation program, is considered an answer to the prison and public radicalization. Nevertheless, despite burgeoning literature on de-radicalization or rehabilitation, there is one persistent issue remains unaddressed satisfactorily to say the least, that is the content and module of de-radicalization. The issue revolved around the question: ‘what is workable and effective module needed to rehabilitate extremist?’, ‘what is suitable approach needed to make rehabilitation program successful?’. This article attempts to address this question, and seeks to explore the extremist discourse and narratives that serves as the credo of extremism. Second, it explores and advance Wasatiyyah approach as counter-discourse to extremism and how it can be applied effectively in de-radicalization context.